Pengaruh Literasi Keuangan, Gaya Hidup, dan Pendapatan terhadap Pengelolaan Keuangan Keluarga di Desa Sudimoro Timbulharjo Sewon - Ariandini, Athir; Hermuningsih, Sri; Wiyono, Gendro (Fakultas Ekonomi Universitas Samudra, 2024)
The aim of this research is to understand the implementation of financial management in families in Sudimoro Timbulharjo Sewon Village, Bantul Regency, using 100 respondents as a sample. Research results prove that financial literacy has a positive and significant impact on family financial management; lifestyle has a negative and insignificant impact on financial management; and, income has a positive and insignificant impact on family financial management. Based on the results obtained, it is recommended that families understand the importance of efforts to increase knowledge about financial literacy, lifestyle, and understand income correctly to manage finances in the family.